The Relationship Between Glaucoma Duration and Quality of Life Among Patients at Haji General Hospital Medan - Putri Fariha Munthadziroh; Zaldi Zaldi (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: Glaucoma is one of the leading causes of blindness in the world, with its prevalence increasing every year. The decline in vision function resulting from glaucoma has an impact on various aspects of daily life, such as mobility, emotional well-being, and social activities. Method: This study used a cross-sectional design with a population of glaucoma patients who were treated at Haji General Hospital Medan. Sampling was carried out purposively. Data were collected using a validated NEI-VFQ-25 questionnaire. Data analysis is carried out with appropriate statistical tests to determine the relationship between independent and dependent variables. Results: The result of the analytical test, p 0.05 was obtained, so it was proven that there was a long-term relationship between suffering from glaucoma and the quality of life of glaucoma patients. The results of Pearson's analysis were -0.451 where the correlation was stated to be reversed and the correlation level was moderate. Discussion: The correlation found was inversely proportional with a moderate correlation rate, meaning that the longer patients had glaucoma, their quality of life was likely to decline. These findings emphasize the importance of early detection and appropriate treatment to minimize the negative impact of glaucoma on patients' quality of life.